STL-seq reveals pause-release and termination kinetics for promoter-proximal paused RNA polymerase II transcripts - Zimmer, Joshua T.; Rosa-Mercado, Nicolle A.; Canzio, Daniele; Steitz, Joan A.; Simon, Matthew D. (Molecular cell, 2021)
Despite the critical regulatory function of promoter-proximal pausing, the influence of pausing kinetics on transcriptional control remains an active area of investigation. Here, we present Start-TimeLapse-seq (STL-seq), a method that captures the genome-wide kinetics of short, capped RNA turnover and reveals principles of regulation at the pause site. By measuring the rates of release into elongation and premature termination through the inhibition of pause release, we determine that pause-release rates are highly variable, and most promoter-proximal paused RNA polymerase II molecules prematurely terminate (∼80%). The preferred regulatory mechanism upon a hormonal stimulus (20-hydroxyecdysone) is to influence pause-release rather than termination rates. Transcriptional shutdown occurs concurrently with the induction of promoter-proximal termination under hyperosmotic stress, but paused transcripts from TATA box-containing promoters remain stable, demonstrating an important role for cis-acting DNA elements in pausing. STL-seq dissects the kinetics of pause release and termination, providing an opportunity to identify mechanisms of transcriptional regulation. [Display omitted] •STL-seq measures the kinetics of promoter-proximal paused Pol II transcripts•Four of five initiated transcripts are terminated at the pause site on average•Cell signaling regulates release into elongation to alter gene expression•Hyperosmotic stress induces termination at pause sites of TATA-less promoters Zimmer et al. report an RNA-sequencing method, STL-seq, which captures the steady-state dynamics of promoter-proximal pausing. The authors use STL-seq to dissect the effects of release into elongation and premature termination on Pol II-pausing dynamics and to reveal the principles of regulation at the pause site.